TINJAUAN ASPEK ARSITEKTUR KOLONIAL DAN NILAI HISTORIS BANGUNAN LANDRAAD TE PURBALINGGA SEBAGAI SALAH SATU BANGUNAN LAMA YANG MASIH LESTARI - Moh Sepul Bahri; Ariija Nayla Farha; Haris Rahman; Rifan Dwi Wijayakusuma (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
This research examines the colonial architectural elements and historical values of the Landraad te Purbalingga building as one of the surviving colonial heritages in Indonesia. The purpose of this research is to identify the colonial architectural characteristics applied in this building and to examine the related historical values, both in functional aspects and social symbiolism. The method applied is a descriptive literary approach by conducting field observations, conducting in-depth interviews with relevant sources, and analyzing existing documentation. The results indicate that the Landraad te Purbalingga building still retains a number of colonial architectural elements, such as high ceilings, large windows, teak doors, and minimalist-style columns, although some parts have undergone changes due to renovations and functional adjustments. Historically, the building served as a special court for natives during the colonial period, reflecting the practice of legal discrimination and social segregation. The preservation efforts undertaken to date emphasize the importance of maintaining collective memory and local identity through physical preservation as well as the historical value of the building. This research is expected to serve as a basis for efforts to preserve and utilize historic buildings in small towns in Indonesia.